Frequency and predictors for early-achieved lupus low disease activity state in systemic lupus erythematosus patients treated with telitacicept or belimumab: A real-life, single-center observational study - Fan, Cuiling; Yang, Tao; Zheng, Songyuan; Liao, Xiaozhong; Xie, Ruixia; Chen, Shixian; Li, Juan (Frontiers in Immunology, 2024)
Objective: To collect real-world data regarding the attainment of the early-achieved lupus low disease activity state (LLDAS) in systemic lupus erythematosus (SLE) patients receiving telitacicept or belimumab treatment, and identify factors predictive of target achievement. Methods: Eighty-seven SLE patients who received telitacicept (N=42) or belimumab (N=45) were retrospectively reviewed in this observational study. Clinical and laboratory data, disease activity assessment, and glucocorticoid dosage were collected for analysis. Achieving LLDAS at least once within 24 weeks post-treatment was considered as early-achieved LLDAS. Multivariate regression was used to assess baseline predictive variables for early-achieved LLDAS. Subgroup analysis and interaction tests were also performed to examine the robustness of the results across different sets of baseline characteristics. Prognostic stratification for early-achieved LLDAS was established based on the identified risk factors. Results: During the 24-week follow-up period, LLDAS was achieved by at least one time in 49.43% (43/87) of the patients, with sustained achievement through week 24 observed in 36 out of these 43 patients (83.27%). Multivariate analysis revealed that early achievement of LLDAS was particularly observed in patients with higher baseline lymphocyte counts ［ HR=1.79, 95% CI (1.19-2.67), P=0.005 ］ and serum albumin levels ［ HR=1.06, 95% CI (1.003-1.12), P=0.039. Conversely, hematological involvement［HR=0.47, 95% CI (0.24-0.93), P=0.031］predicted lower attainment of early-achieved LLDAS. The use of telitacicept was associated with a reduced risk of failing to attain early achievement of LLDAS［HR=2.55, 95% CI (1.36-4.8), P=0.004］ . Subgroup analyses and interaction tests showed a stable relationship between the telitacicept use and LLDAS achievement. The results remained consistent across all subgroup analyses. Significant differences (P<0 .001) were observed in the Kaplan-Meier estimates for LLDAS among risk groups based on the number of identified risk factors.The achievement of LLDAS is attainable in the management of SLE patients undergoing treatment with telitacicept or belimumab in real-life clinical practice. Baseline lymphocyte counts, serum albumin levels, hematological involvement and the use of telitacicept serve as robust predictors for early-achieved LLDAS, helping to identify patients who are likely to benefit on the treatment.